Linking sedentary behavior and mental distress in higher education: a cross-sectional study - Subiron-Valera, Ana Belen; Rodriguez-Roca, Beatriz; Calatayud, Estela; Gomez-Soria, Isabel; Andrade-Gómez, Elena; Marcen-Roman, Yolanda (Frontiers in Psychology, 2023)
Background Sedentary behavior among university students could negatively affect their mental health. Objective The aim of this study was to examine the relationship of mental health (anxiety and depression) and sedentary behavior between gender in Health Degrees at the University of Zaragoza. Design Cross-sectional descriptive study. Participants Sample of 257 University students who completed an online questionnaire. Methods Sedentary behavior was assessed with the SBQ questionnaire. Anxiety and depression were assessed with the GADS questionnaire. The Mann–Whitney U test and multiple linear regression models were used. Results In comparison to men, female students with symptoms of anxiety spend more time in total engaged in sedentary behaviors (10.56 ± 4.83) vs. (7.8 ± 3.28; p < 0.001) and mentally-passive sedentary activities [2.24 (1.57) vs. 1.15 (0.90; p < 0.005)]. Female students at risk of depression also spend more hours engaged in mentally-passive sedentary behaviors in comparison to men (8.28 ± 50.70 vs. 1.27 ± 1.02; p = 0.009). Conclusion Female students at risk of anxiety and/or depression spend more time engaged in sedentary activities in comparison to male students. The risk of anxiety and depression is associated with the total number of hours a day spent engaged in sedentary behaviors and with mentally passive behaviors, but not mentally active behaviors.